A comparative study on the management mode of Chinese and foreign universities in cooperative education - Gao, Menghan (International Journal of Global Economics and Management, 2024)
The purpose of this study is to compare the management modes of Chinese and foreign universities, analyze their advantages and challenges, and explore how to improve the quality of higher education under the background of globalization. Firstly, the research summarizes the development background of Sino-foreign cooperative education, and then reveals the application and effect of different management concepts and methods in practice through the comparative analysis of cooperation modes between Chinese and foreign universities. It is found that although international cooperation has obvious advantages in resource sharing and education quality improvement, it also faces challenges such as cultural differences and inconsistent management systems. This study discusses in detail the specific practices of several Chinese-foreign cooperative universities by case analysis, including management structure, teaching methods and quality assurance mechanism. Finally, some suggestions are put forward to optimize the management mode of cooperative education, so as to promote the in-depth development of cooperation between Chinese and foreign universities.